Pseudomonas aeruginosa PAO1 preferentially grows as aggregates in liquid batch cultures and disperses upon starvation. - David Schleheck; Nicolas Barraud; Janosch Klebensberger; Jeremy S Webb; Diane McDougald; Scott A Rice; Staffan Kjelleberg (PLoS ONE)
In both natural and artificial environments, bacteria predominantly grow in biofilms, and bacteria often disperse from biofilms as freely suspended single-cells. In the present study, the formation and dispersal of planktonic cellular aggregates, or 'suspended biofilms', by Pseudomonas aeruginosa in liquid batch cultures were closely examined, and compared to biofilm formation on a matrix of polyester (PE) fibers as solid surface in batch cultures. Plankton samples were analyzed by laser-diffraction particle-size scanning (LDA) and microscopy of aggregates. Interestingly, LDA indicated that up to 90% of the total planktonic biomass consisted of cellular aggregates in the size range of 10-400 microm in diameter during the growth phase, as opposed to individual cells. In cultures with PE surfaces, P. aeruginosa preferred to grow in biofilms, as opposed to planktonicly. However, upon carbon, nitrogen or oxygen limitation, the planktonic aggregates and PE-attached biofilms dispersed into single cells, resulting in an increase in optical density (OD) independent of cellular growth. During growth, planktonic aggregates and PE-attached biofilms contained densely packed viable cells and extracellular DNA (eDNA), and starvation resulted in a loss of viable cells, and an increase in dead cells and eDNA. Furthermore, a release of metabolites and infective bacteriophage into the culture supernatant, and a marked decrease in intracellular concentration of the second messenger cyclic di-GMP, was observed in dispersing cultures. Thus, what traditionally has been described as planktonic, individual cell cultures of P. aeruginosa, are in fact suspended biofilms, and such aggregates have behaviors and responses (e.g. dispersal) similar to surface associated biofilms. In addition, we suggest that this planktonic biofilm model system can provide the basis for a detailed analysis of the synchronized biofilm life cycle of P. aeruginosa.